Pelatihan Bisnis dan Wirausaha pada Unit Usaha Kecil dan Menengah dalam Menciptakan Ketahanan Ekonomi - Arsyad Sumantika; Yudi Kornelis; Riswandi Riswandi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
There are several problems that arise in the process of community service, especially related to a lack of knowledge about business fields and effective marketing strategies. Knowledge about innovation and sales knowledge are the basic foundations for carrying out entrepreneurial activities, if not carried out well entrepreneurial activities will not be as expected. In this service, the implementing team provides education regarding entrepreneurial activities. The method used is participatory in activities such as group discussions, interviews, consultations and determining action decisions. The implementation of this activity involves the participation of several communities in the Batu Aji, Batam region. The implementation of this activity includes several stages, which are planning, implementation of activities and evaluation. In community service activities, this training has had a positive impact on the people, where many people try to run businesses from home using the available resources around them. In addition, the application of social networks in marketing activities becomes even more effective in creating sustainable revenue sources and expanding markets.